Extrinsic and intrinsic apoptosis activate pannexin‐1 to drive NLRP3 inflammasome assembly. (22nd March 2019) - Chen, Kaiwen W; Demarco, Benjamin; Heilig, Rosalie; Shkarina, Kateryna; Boettcher, Andreas; Farady, Christopher J; Pelczar, Pawel; Broz, Petr
Abstract: Pyroptosis is a form of lytic inflammatory cell death driven by inflammatory caspase‐1, caspase‐4, caspase‐5 and caspase‐11. These caspases cleave and activate the pore‐forming protein gasdermin D (GSDMD) to induce membrane damage. By contrast, apoptosis is driven by apoptotic caspase‐8 or caspase‐9 and has traditionally been classified as an immunologically silent form of cell death. Emerging evidence suggests that therapeutics designed for cancer chemotherapy or inflammatory disorders such as SMAC mimetics, TAK1 inhibitors and BH3 mimetics promote caspase‐8 or caspase‐9‐dependent inflammatory cell death and NLRP3 inflammasome activation. However, the mechanism by which caspase‐8 or caspase‐9 triggers cell lysis and NLRP3 activation is still undefined. Here, we demonstrate that during extrinsic apoptosis, caspase‐1 and caspase‐8 cleave GSDMD to promote lytic cell death. By engineering a novel Gsdmd D88A knock‐in mouse, we further demonstrate that this proinflammatory function of caspase‐8 is counteracted by caspase‐3‐dependent cleavage and inactivation of GSDMD at aspartate 88, and is essential to suppress GSDMD‐dependent cell lysis during caspase‐8‐dependent apoptosis. Lastly, we provide evidence that channel‐forming glycoprotein pannexin‐1, but not GSDMD or GSDME promotes NLRP3 inflammasome activation during caspase‐8 or caspase‐9‐dependent apoptosis. Synopsis: The apoptotic signalling cascade promotes NLRP3 inflammasome assembly by activating the channel‐forming glycoprotein, pannexin‐1. Extrinsic apoptosis promotes caspase‐1 and ‐8‐dependent GSDMD activation in parallel with caspase‐3/7‐dependent secondary necrosis. Caspase‐3 suppresses GSDMD‐dependent cell lysis during extrinsic apoptosis. GSDME is activated during extrinsic and intrinsic apoptosis, but it does not contribute to cell lysis in macrophages. NLRP3 assembly during extrinsic and intrinsic apoptosis is dependent on pannexin‐1 but not gasdermin D or E pores. Abstract : Caspase‐8/9‐mediated apoptosis avoids lytic cell death despite initial gasdermin cleavage, with inflammasome activation instead being driven by the channel‐forming glycoprotein pannexin.